Senam Ergonomik dan Aerobic Low Impact Menurunkan Tekanan Darah Pada Lansia Hipertensi - Revansia Missi Perdana; Arina Maliya (Jurnal Berita Ilmu Keperawatan, 2017)
The many changes that occur in the elderly many health problems facing so it is necessary to maintain the health of the attempts both treatments, medication, healthy lifestyle, as well as other efforts such as gymnastics ergonomics and low impact aerobics. The purpose of the study to determine the effectiveness of aerobic exercise ergonomics and little impact on blood pressure levels in the Elderly Hypertension at Wironanggan Village, District Gatak Sukoharjo.The research method used was a quasi-experimental design with the design of non-equivalent control group design. The population was all patients with hypertension of 7 Posyandu Wironanggan. As many as 80 elderlies who suffer from hypertension, taken 44 participants were divided into two experimental groups, namely experimental group 1 were 22 people, and the experimental group 2 to 22 people with a purposive sampling technique. The variable independent variable in this study gymnastics ergonomics and low impact aerobics and the dependent variable is the level of blood pressure by using electric tension instruments — the analysis techniques with simple paired t-test and independent t-test. The results showed there are differences in the effect of exercise ergonomics and low impact aerobics to the pressure level blood systolic and diastolic hypertension in the elderly, and the most effective influence on the ergonomics exercise systolic pressure and low impact aerobic exercise on diastolic blood pressure.